The in vivo effect of lipopolysaccharide on the spontaneous release of transmitter from motor nerve terminals. - Liu, S. H. (1995)
1. The in vivo effect of E. coli lipopolysaccharide (LPS) on the spontaneous release of transmitter was studied in the isolated phrenic nerve-diaphragm preparation of the mouse. 2. The resting membrane potential was decreased and frequency of miniature endplate potentials (m.e.p.ps) was increased by treatment with LPS. 3. Pretreatment of diaphragms with ouabain markedly increased the frequency of m.e.p.ps in control group but not in the LPS group. 4. When mice were treated with polymyxin B (a LPS neutralizer), pentoxifylline (an inhibitor of tumor necrosis factor-alpha formation) and NG-nitro-L-arginine (an inhibitor of nitric oxide (NO) synthase) the effects of LPS were reversed. 5. These results suggest that LPS increases the spontaneous transmitter release through, at least in part, the pathways of tumour necrosis factor-alpha and NO followed by an inhibition of the Na(+)-pump activity in the endplate area.